2014
DOI: 10.1128/jvi.01815-14
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking of Bluetongue Virus Visualized by Recovery of Tetracysteine-Tagged Virion Particles

Abstract: Bluetongue virus (BTV), a member of the Orbivirus genus in the Reoviridae family, is a double-capsid insect-borne virus enclosing a genome of 10 double-stranded RNA segments. Like those of other members of the family, BTV virions are nonenveloped particles containing two architecturally complex capsids. The two proteins of the outer capsid, VP2 and VP5, are involved in BTV entry and in the delivery of the transcriptionally active core to the cell cytoplasm. Although the importance of the endocytic pathway in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 53 publications
(89 reference statements)
0
32
0
Order By: Relevance
“…This suggested that the 100kDa protein fragment lacked the first 94 amino acids. With an exposed loop identified, the TC tag was inserted, for subsequent determination of whether its introduction still preserved overall folding and biological activity (14).…”
Section: Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggested that the 100kDa protein fragment lacked the first 94 amino acids. With an exposed loop identified, the TC tag was inserted, for subsequent determination of whether its introduction still preserved overall folding and biological activity (14).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The power of this technology was demonstrated through the enabling of the delineation of the dynamics of the two outer capsid proteins, which were shown to dissociate from one another during the early stages of virus entry into mammalian cells (14). Here we describe the prerequisite methodology that led to this observation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One well characterized small tag is the 6‐amino acid tetracysteine (TC) tag, which can be labelled with biarsenical dyes (FLAsH). Successful visualization using the TC tag has been shown for HIV , alphavirus , bluetongue virus and HCV . For HBV, the TC tag has been incorporated into the core protein, and virus particles labelled with a biarsenical dye were secreted into the medium .…”
Section: Applications Of Labelling and Visualization Techniques To Unmentioning
confidence: 99%
“…FlAsH-EDT2 was first described in 1998 and was shown to fluoresce when bound to two pairs of cysteines separated by two amino acids (CCXXCC), referred to as a tetracysteine (TC) tag (22). This technique has been utilized in several recombinant viruses, including HIV-1, to visualize TC-Gag protein during infection, and in bluetongue virus, a member of the Reoviridae family, to label viral protein VP2 to visualize virus particle entry (23,24). Once the TC tag is added to a protein, FlAsH-EDT2, which contains two 1,2-ethanedithiol motifs, creates covalent bonds with the TC motif, resulting in fluorescence.…”
mentioning
confidence: 99%